Circulating B cells in type 1 diabetics exhibit fewer maturation-associated phenotypes - Hanley, Patrick; Sutter, Jennifer A.; Goodman, Noah G.; Du, Yangzhu; Sekiguchi, Debora R.; Meng, Wenzhao; Rickels, Michael R.; Naji, Ali; Luning Prak, Eline T. (Clinical immunology (Orlando, Fla.), 2017)
Although autoantibodies have been used for decades as diagnostic and prognostic markers in type 1 diabetes (T1D), further analysis of developmental abnormalities in B cells could reveal tolerance checkpoint defects that could improve individualized therapy. To evaluate B cell developmental progression in T1D, immunophenotyping was used to classify circulating B cells into transitional, mature naïve, mature activated, and resting memory subsets. Then each subset was analyzed for the expression of additional maturation-associated markers. While the frequencies of B cell subsets did not differ significantly between patients and controls, some T1D subjects exhibited reduced proportions of B cells that expressed transmembrane activator and CAML interactor (TACI) and Fas receptor (FasR). Furthermore, some T1D subjects had B cell subsets with lower frequencies of class switching. These results suggest circulating B cells exhibit variable maturation phenotypes in T1D. These phenotypic variations may correlate with differences in B cell selection in individual T1D patients.